Exploratory meta-analysis on lisdexamfetamine versus placebo in adult ADHD - Maneeton,N. (Dove Medical Press Ltd., 2015)
© 2014 Maneeton et al. Results: A total of 806 final study or safety participants were included. The dosage of lisdexamfetamine was 30 to 70 mg/day. The pooled mean scores of mean change and mean end point scores between LDX- and placebo-treated groups also had a significant difference (SMD [95% CI] of -0.97 [-1.15, -0.78], I2=18%). The pooled response rates for adult ADHD between the two groups had a significant difference (RR [95% CI] of 1.99 [1.50, 2.63], I2=0%). Based on the Behavior Rating Inventory of Executive Function – Adult version (BRIEF-A), the pooled end point mean scores for the Global Executive Composite (GEC) for the LDX-treated groups was greater than that of placebo-treated groups (MD [95% CI] of –9.20 [-14.11, -4.29], I2=34%). The pooled overall discontinuation rates between the two groups had no significant difference (RR [95% CI] of 0.82 [0.59, 1.14], I2=0%). Similarly, the pooled discontinuation rates due to adverse events between the two groups was not significantly different (RR [95% CI] of 1.77 [0.71, 4.40], I2=0%). Conclusion: The number of included studies was limited (five RCTs), but based on this meta-analysis, LDX is efficacious and well tolerated in the treatment of adult ADHD. Additionally, it also improved the executive function deficits in this population. However, its acceptability is no higher than placebo. These findings should be carefully interpreted and considered as preliminary outcomes. To confirm these results, further studies are warranted. LDX is a viable alternative psychostimulant for adult ADHD. Methods: The database of MEDLINE®, EMBASE™, CINAHL®, PsycINFO® and Cochrane Controlled Trials Register were searched in January 2014. Studies were also searched in ClinicalTrials.gov and the EU Clinical Trials Register database. Study eligibility criteria, participants, and interventions were considered. All RCTs of LDX vs placebo reporting final results of: 1) severity of ADHD symptoms and executive function deficit, 2) response or remission rates, 3) overall discontinuation rate, or 4) discontinuation rate due to adverse events were included. The language of the papers was not restricted. All abstracts of studies gathered from the database were examined. After excluding irrelevant trials, the full text version of relevant studies were assessed and extracted for outcomes of interest. Examination of risks of bias, based on the Cochrane bias assessment, was carried out. The efficacy outcomes consisted of the mean end point or change scores for ADHD rating scales, the response rate, and the remission rate. The overall discontinuation rate and the discontinuation rate due to adverse events were measured for acceptability and tolerability, respectively. A random effect model was applied for the synthesis of relative risks (RRs), and weighted mean differences or standardized mean differences (SMDs) with 95% confidence intervals (CIs). Objectives: This systematic review was undertaken to summarize LDX efficacy, acceptability, and tolerability in adult ADHD. All randomized controlled trials (RCTs) of lisdexamfetamine compared with placebo were included for synthesis. Clinical trials published between January 1991 and January 2014 were evaluated. Background: Recent studies have promised that lisdexamfetamine (LDX) is effective in the treatment of adults with attention-deficit hyperactivity disorder (ADHD).